2016
DOI: 10.1111/cfs.12301
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve supervised contact visits between children in out of home care and their parents: a systematic review

Abstract: Although the importance of contact between children in care and their parents, when safe, is accepted, there is limited research about supervised face‐to‐face contact. There is no literature that has systematically critiqued how supervised contact can be best delivered. The aim of this systematic review was to evaluate the evidence for interventions aimed at improving the quality of contact visits between parents and their children who are in out‐of‐home care. Twelve studies were included in this review. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
1
16
0
3
Order By: Relevance
“…In developing such an instrument, it would be useful to incorporate a dyadic analysis of the parent–child relationship (La Valley & Guerrero, 2012). In addition, and in line with previous research (Bullen et al, 2017; Höjer 2009; Nesmith, Patton, Christophersen, & Smart, 2017), our findings highlight the need to provide birth parents with training, support, and information that can assist them in contact visits and improve family relationships in the context of foster care. We are currently in the process of designing a training program aimed at both birth parents and foster carers that seeks to meet these goals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In developing such an instrument, it would be useful to incorporate a dyadic analysis of the parent–child relationship (La Valley & Guerrero, 2012). In addition, and in line with previous research (Bullen et al, 2017; Höjer 2009; Nesmith, Patton, Christophersen, & Smart, 2017), our findings highlight the need to provide birth parents with training, support, and information that can assist them in contact visits and improve family relationships in the context of foster care. We are currently in the process of designing a training program aimed at both birth parents and foster carers that seeks to meet these goals.…”
Section: Discussionsupporting
confidence: 90%
“…The question of whether parental contact is beneficial does not have a clear-cut answer (Bullen, Taplin, Kertesz, Humphreys, & McArthur, 2015;Quinton, Rushton, Dance, & Mayes, 1997). Some studies have concluded that visits with birth parents can promote the child's social and emotional development and well-being (Berridge, 1997;McWey & Cui, 2017;McWey & Mullis, 2004;Schofield & Beek, 2009;Schofield & Ward, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The informants had several examples of how they tried both to keep distance and to spend time with their parents. Professional support in families who do not live together could contribute to making contact between children and parents safe and confident and may prevent children's experience of loneliness and insecurity (Bullen, Taplin, McArthur, Humphreys, & Kertesz, 2017;Taplin & Mattick, 2014).…”
Section: A Double Challenge For Professionalsmentioning
confidence: 99%
“…Triseliotis concludes by commenting that the entire process of contact has inherent difficulties that, on the one hand condemn birth parents for failing to engage proactively with their child, and on the other, may criticise them for being far too dominant. In their literature review on supervised contact, Bullen and colleagues (2015) further substantiate Triseliotis’s perspective by indicating that the evidence base for such judgements about quality of birth parent–child interaction during supervised contact is considerably thin. They echo his observation of the ability for social work practitioners to assess and judge the quality of contact in the absence of empirically based guidelines and a standardised framework.…”
Section: New Research Insights and Real And Virtual World Developmentsmentioning
confidence: 86%